An evaluation of the prevalence of HIV/AIDS on selected economies of sub-Saharan Africa - Raji Abdulghafar Bello; Gafar Tunde Ijaiya (AOSIS, 2012)
Human immunodeficiency syndrome (HIV) whose full-blown period is called acquired immunity deficiency syndrome (AIDS) is today a terminal disease. While one weakens the body hormones, the other comes to claim the life with its accompanying opportunistic diseases. Several factors have been reviewed to be causing the infection and its prevalence as well as its socio-economic, scientific and cultural dimensions. The cost implication of this ailment is enormous when considered from individual, national or global perspective, especially when the cost of treatment and the cost of the disability adjusted life years (DALYs) lost to incapacitation from HIV/AIDS is considered. This study has investigated the financial implications of treatment and the DALYs lost to HIV/AIDS from the perspective of sub-Saharan Africa covering thirty-five countries. Infected population of age 15-49 years were considered, being the active life year age group. Applying Morrow's DALYs measurement, and Ainsworth's per capita general rule method of costing HIV/AIDS, it was found that the cost of treatment of HIV/AIDS in any country depends on her economic strength on the one hand and the size of the infected population on the other, to the extent that no country spends or loses less than 3 percent of her national income on treatment and to DALYs. To any country, the financial cost of the DALYs lost to HIV/AIDS is much more than the cost of treatment per episode, mostly huge enough to develop a sector of the country's economy. However, a single recommendation could be difficult as individual countries experience different effect, but different countries must pursue long-run anti-prevalence policies individually and as economic region or bloc.